CMV Encephalitis/Radiculitis: The Difficulty in Diagnosing in an Intubated Patient - Geoffrey Newcomb; Peter Mariuz; Daniel Lachant (Case Reports in Critical Care)
Cytomegalovirus (CMV) can cause severe disease including colitis, pneumonitis, and less commonly encephalitis, in profoundly immunocompromised individuals. CNS imaging findings are nonspecific and diagnosis is made by identifying CMV in cerebral spinal fluid through PCR testing or cell culture. Early initiation of antiviral therapy is key with an overall poor outcome. Here we present a patient with newly diagnosed AIDS and pneumocystis jiroveci pneumonia who was febrile and remained encephalopathic for the first 6 weeks of his admission despite treatment and extensive work up for encephalopathy. Ultimately, he was diagnosed with CMV encephalitis and radiculitis and failed to improve significantly. This case is important because of multiple points (1) the uncommon presentation of CMV encephalitis/radiculitis occurring over 1 month into a hospitalization; (2) in the era of highly active antiretroviral therapy (HAART) severe complications of AIDS are rarely seen by newer generations of physicians and are not typically thought of; (3) the difficulties in evaluating altered mental status and weakness in an intubated patient receiving sedation. In immunosuppressed patients on mechanical ventilation, early evaluation with LP should be considered when altered mental status and fever of unclear etiology are present.